2022
DOI: 10.1039/d2bm00518b
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency brain-targeted intranasal delivery of BDNF mediated by engineered exosomes to promote remyelination

Abstract: The regeneration of myelin sheath is the ultimate therapeutic goal of demyelination disease, including multiple sclerosis (MS). However, current drugs for MS mainly targeting the immune system, which can only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…Interestingly, the effect was observed at low doses of Bryo-2 (1 × 10 8 particles) when encapsulated in the EVs compared to the systemic delivery of Bryo-1 alone . The regeneration of myelin sheaths and improved motor abilities were also achieved when BDNF-loaded EVs were delivered in the mice models of MS . Here, the authors mainly highlight the mode of EV delivery (intranasal) to increase the efficiency of the therapy, suggesting that the delivery modes also impact EV functioning and availability to the targeted site.…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effect was observed at low doses of Bryo-2 (1 × 10 8 particles) when encapsulated in the EVs compared to the systemic delivery of Bryo-1 alone . The regeneration of myelin sheaths and improved motor abilities were also achieved when BDNF-loaded EVs were delivered in the mice models of MS . Here, the authors mainly highlight the mode of EV delivery (intranasal) to increase the efficiency of the therapy, suggesting that the delivery modes also impact EV functioning and availability to the targeted site.…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
“…Interestingly, the effect was observed at low doses of Bryo-2 (1 × 10 8 particles) when encapsulated in the EVs compared to the systemic delivery of Bryo-1 alone. 221 The regeneration of myelin sheaths and improved motor abilities were also achieved when BDNFloaded EVs were delivered in the mice models of MS. 222 Here, the authors mainly highlight the mode of EV delivery (intranasal) to increase the efficiency of the therapy, suggesting that the delivery modes also impact EV functioning and availability to the targeted site. Apart from the neural origin, EVs from other cell types are also shown to mediate neuroprotection in MS. For instance, Jia et al overexpressed the Treg gene FOXP3 in the dendritic cells and observed that the exosomes released from them, when cocultured with CD4+ cells, could suppress their proliferation and immune phenotype.…”
Section: Autoimmune Diseases 341 Multiple Sclerosismentioning
confidence: 99%
“…However, BDNF has a poor ability to cross the BBB. Recently, our study successfully loaded the mRNA and protein of BDNF onto exosomes, which can promote the differentiation of OPCs into mature oligodendrocytes in vitro and had a significant therapeutic effect on remyelination and motor coordination ability improvement in demyelination model mice via intranasal administration [42]. Another study also proved that BDNF could be loaded onto exosomes derived from BDNF-overexpressing HEK293 cells, regulating the internal cellular environment and inhibiting apoptosis [43].…”
Section: Exosomes In Ms Therapeuticsmentioning
confidence: 84%
“…SLNs and NLPs have shown higher drug loading, better drug stability and prolonged release profile compared to liposomes [ 74 , 75 ]. Finally, exosomes, naturally derived nanocarriers secreted by cells, have recently attracted interest as drug delivery systems for the treatment of brain disorders through IN administration thanks to their low immunogenicity, good biocompatibility, possibility of functionalization for targeted action and broad spectrum of endogenous and exogenous bioactive cargo molecules, including protein, nucleic acids, growth factors and therapeutic agents [ 65 , 67 , 76 ]. Interestingly, the nanocarrier surface has been frequently functionalized with: Muco-adhesive polymers such as chitosan or polymer containing thiol groups (thiomers); Molecules for adsorption endocytosis by the epithelial layer (e.g., lectins, cell-penetrating peptides, such as penetratin, Tat peptide, etc.…”
Section: Biomaterials-based Vehicles For In Drug Deliverymentioning
confidence: 99%
“…Yang et al prepared liposomes loaded with rivastigmine and surface functionalized with a cell-penetrating peptide [ 64 ]. Zhai et al modified the surface of exosomes with rabies virus glycoprotein (RVG) peptide able to specifically bind to neuronal acetylcholine receptor for the delivery of brain-derived neurotrophic factor for multiple sclerosis applications [ 67 ]. Finally, Peng et al proposed a novel nanocarrier system, characterized by a polymer micellar core composed of PPS−PEG, encapsulated in an exosome outer shell modified with penetratin and RVG peptides for the delivery of curcumin for Parkinson’s disease treatment [ 66 ].…”
Section: Biomaterials-based Vehicles For In Drug Deliverymentioning
confidence: 99%